367. RANDOMISED CONTROLLED TRIAL (FEASIBILITY STUDY) OF PROPHYLACTIC PYLORIC BALLOON DILATATION DURING IVOR LEWIS ESOPHAGECTOMY TO PREVENT DELAYED GASTRIC EMPTYING. (24th September 2022) - Abdelrahman, Mohamed; Neilens, Helen; Yates, Victoria; Lord, Amber; Ariyarathenam, Arun; Berrisford, Richard; Humphreys, Lee; Sanders, Grant; Wheatley, Tim; Chan, David
Abstract: Early delayed gastric emptying (DGE) occurs in up to 37% of patients following esophagectomy. This can contribute to increased anastomotic leak and respiratory infection rates. Although the treatment of DGE in the form of pyloric balloon dilatation (PBD) post-operatively is well established, there is no consensus on the optimal approach in the prevention of DGE. The aim is to carry out a randomised control trial to determine the efficacy of prophylactic PBD in the prevention of DGE following esophagectomy. This presentation details the protocol, recruitment strategy and potential timeline for a feasibility study addressing this. We detail the rationale, objectives, design, and methods of this study. Patients will be recruited over a three to six-month period (starting in January 2022) and randomised to either a control group (no intervention) or a treatment group (prophylactic PBD). The Chief Investigator has obtained approval from the UK Health Research Authority (HRA) and Research Ethics Committee (REC) on 01/12/21 (IRAS project ID: 287659). As a feasibility study, the objectives will be to ascertain the following: Number of patients approached; Number of patients who agreed to be randomised; Number of patients successfully randomised; Number of patients who dropped out; Successful measurement of outcome measures (delayed gastric emptying, pneumonia, anastomotic leak). Prophylactic pyloric balloon dilatation is potentially a safe and effective procedure which can significantly improve outcomes in patients after an esophagectomy. This protocol describes details for the feasibility study to be carried out which will allow important learning points for the main randomised controlled trial.